O professor coordenador e os desafios na constituição de uma identidade no desenvolvimento profissional: um fazer real e possível - Oliveira, Daniela Claro de (2016)
This research had for objective, to analyze the process of the coordinating teacher of the cycle of the final years of formation of the Management of North Regional Teaching 1 of the from São Paulo state net, to investigate as the coordinators plans their actions and daily practices starting from the formation that they participate monthly, organized for the section of the Pedagogic Nucleus of this management and to address the importance of a formation proposal to come to provide the coordinating teacher professional development for the construction of former role. In this work we intended to contemplate on her the formative process and their formative needs, under the coordinators' optics. Of the methodological point of view, the present work was developed according to the methodology of the qualitative perspective. It was possible to identify in the group of the analyzed data (rising through interview semistructured) the coordinating teachers' voices in relation to the accomplished formations, a lot of times, it was not in keeping with what was waited in practice as for the professional development as former. It is in this context that is done necessary a formation proposal, that contributes to a professional development and the constitution of an identity in a practice educational former that goes very beyond, demanding an attitude more open epistemological, come back more in the sense from looking and of listening in an action collaborative